Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5535/arm.20180
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Aspiration Pneumonia in the Elderly With Swallowing Dysfunction: Videofluoroscopic Swallowing Study

Abstract: Objective To identify the variables of videofluoroscopic swallowing study (VFSS) that are useful for predicting the risk of aspiration pneumonia in elderly patients with dysphagia.Methods A total of 251 patients (aged 65 years or more) were included and divided into a pneumonia group (n=133) and a non-pneumonia group (n=118). The pneumonia group included patients who had been diagnosed with aspiration pneumonia, and individuals in the non-pneumonia group did not have pneumonia but were referred for VFSS. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…A previous study found out that MPT is associated with triggering of pharyngeal swallowing and laryngeal elevation in Parkinson's disease [25]. Another previous study showed that prolonged pharyngeal transit time is a significant predictor of aspiration pneumonia in the elderly [26]. This is consistent with our study results, showing that MPT had a negative correlation with triggering of pharyngeal swallow, delayed pharyngeal transit time, and laryngeal elevation, which are important airway protective mechanism during deglutition.…”
Section: Correlation Between Mpt With Oral and Pharyngeal Dysphagia P...supporting
confidence: 92%
“…A previous study found out that MPT is associated with triggering of pharyngeal swallowing and laryngeal elevation in Parkinson's disease [25]. Another previous study showed that prolonged pharyngeal transit time is a significant predictor of aspiration pneumonia in the elderly [26]. This is consistent with our study results, showing that MPT had a negative correlation with triggering of pharyngeal swallow, delayed pharyngeal transit time, and laryngeal elevation, which are important airway protective mechanism during deglutition.…”
Section: Correlation Between Mpt With Oral and Pharyngeal Dysphagia P...supporting
confidence: 92%
“…Regarding the relationship with other evaluations, a correlation was found between pyriform sinus residue and swallowing reflex initiation in C-Thick. Ko et al [ 25 ] reported that among patients with dysphagia, those with aspiration pneumonia had poor PAS, delayed swallowing reflex, and increased vallecula and pyriform sinus residue. Delayed swallowing reflex increases the risk of residual bolus in the vallecula or pyriform sinus.…”
Section: Discussionmentioning
confidence: 99%
“…5 Additionally, this leads to a compromised swallowing function. 6 Collectively, these factors are referred to as oral frailty, as indicated by Tanaka. 7 Oral frailty contributes to increased penetration, aspiration, and pharyngeal residue, 8 ultimately leading to colonization of the oral cavity and subsequent aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is characterized by various factors, such as diminished occlusal force owing to the loss of teeth, 4 impaired tongue–lip motor function, reduced tongue pressure, and compromised chewing ability 5 . Additionally, this leads to a compromised swallowing function 6 . Collectively, these factors are referred to as oral frailty, as indicated by Tanaka 7 .…”
Section: Introductionmentioning
confidence: 99%